Model Pembelajaran PAI Berbasis Digital Mobile Learning di SMP Masa Pandemi Covid-19 - Ulvia Aini; Abdurrahman Assegaf (Universitas Pesantren Tinggi Darul 'Ulum, 2021)
This article aims to find out how the teacher’s learning design during distance learning in Junior High Schools (SMP). The Covid-19 pandemic certainly has a significant impact on education, especially on the implementation of distance learning. The schedule of learning from home requires teachers and students to take advantage of information and communication technology. One of the schools that utilizes digital-based learning using several learning applications is SMPN 2 Kunjang. Of course, the application is adapted to the teacher’s teaching strategy during distance learning. The applications used in distance learning are WhatsApp, Classroom, Telegram, Quiziz, Google Form, and YouTube. Based on the results of research using interviews, observations, and document studies conducted by the author, the Dick and Carry model is appropriate to use in PAI learning. This is because the Dick and Carry model has stages and a learning development system that can be implemented in accordance with the teacher’s teaching strategy in Islamic Religious Education (PAI) subjects. In addition, the Dick and Carry model has 10 learning steps that are systematically arranged, starting from identification to the evaluation stage.